Minimally Invasive Internal Fixation of Femoral Shaft Fractures—A Biomechanical Study with a Disruptive Technique - Frank Layher (MDPI AG, 2021)
(1) Background: In polytrauma patients, femur fractures are usually stabilised by external fixation for damage control, later being treated with definitive plate or nail osteosynthesis. Screw/rod systems established in spinal surgery might be inserted for internal fixation, providing sufficient fracture stability that subsequent intervention is unnecessary. This was to be investigated biomechanically. (2) Methods: The unilaterally applied spinal internal fixator (IF) was subjected to load and deformation analysis on artificial femurs with 32-A3 fracture according to AO classification. Distance of screws to fracture and rod to cortical bone were analysed as parameters influenced surgically as stiffness and deformation of the treated fracture. In addition, the stability of another construct with a second screw/rod system was determined. The axial load in stance phase during walking was simulated. The results were compared against an established fixed-angle plate osteosynthesis (IP). (3) Results: There were no implant failures in the form of fractures, avulsions or deformations. All unilateral IF combinations were inferior to IP in terms of stability and stiffness. The bilateral construct with two screw/rod systems achieved biomechanical properties comparable to IP. 4) Conclusion: Biomechanically, a biplanar screw/rod system is suitable for definitive fracture stabilisation of the femur, despite a damage control approach.